Water-in-oil-in-water double emulsion for the delivery of starter cultures in reduced-salt moromi fermentation of soy sauce - Devanthi, Putu Virgina Partha; Linforth, Robert; El Kadri, Hani; Gkatzionis, Konstantinos (Elsevier, 2018)
This study investigated the application of water-oil-water (W1/O/W2) double emulsions (DE) for yeast encapsulation and sequential inoculation of Zygosaccharomyces rouxii and Tetragenococcus halophilus in moromi stage of soy sauce fermentation with reduced NaCl and/or substitution with KCl. Z. rouxii and T. halophilus were incorporated in the internal W1 and external W2 phase of DE, respectively. NaCl reduction and substitution promoted T. halophilus growth to 8.88 log CFU/mL, accompanied with faster sugar depletion and enhanced lactic acid production. Reducing NaCl without substitution increased the final pH (5.49) and decreased alcohols, acids, esters, furan and phenol content. However, the application of DE resulted in moromi with similar microbiological and physicochemical characteristics to that of high-salt. Principal component analysis of GC–MS data demonstrated that the reduced-salt moromi had identical aroma profile to that obtained in the standard one, indicating the feasibility of producing low-salt soy sauce without compromising its quality.